HUBUNGAN INDEKS MASSA TUBUH DENGAN TEKANAN DARAH LANSIA DI PUSKESMAS KAHURIPAN KOTA TASIKMALAYA - Dina Setiawati; Irma Nuraeni; Ima Karimah; H.R Agus Bachtiar (Universitas Tadulako, 2022)
High blood pressure is a non-communicable disease that can cause premature death. The prevalence rate that continues to increase every year makes hypertension the second largest disease in Tasikmalaya City. Overweigth is one of the risk factors for increasing blood pressure in the elderly. The purpose of this study was to determine the relationship between Body Mass Index (BMI) and blood pressure in the elderly at the Kahuripan Health Center, Tasikmalaya City. This type of research is quantitative with a cross-sectional design. The data processed based on the recap of patient visits at the Kahuripan Health Center in August 2021 were 264 patients, then analyzed by the Pearson test. There was no relationship BMI and blood pressure in the elderly. There was a relationship between age and height with diastolic blood pressure in the elderly at the Kahuripan Public Health Center, Tasikmalaya City. It is hoped that this study will provide information related to the risk of hypertension in the elderly at the Kahuripan Health Center, Tasikmalaya City.